Ceo And Organisation Resilience In Dealing With Economic Disruption: A Systematic Review - Anita Ismail; Umi Hamidaton Mohd Soffian Lee (International Journal of Humanities Social Science and Management (IJHSSM), 2024)
Volume 2, Issue 5, pp: 554-566